Escherichia coli, Urinary Tract Infection and Molecular Detection - S Fathollahi; R Yousefi-Mashouf; MT Goodarzi; M Hajilooei; A Mostafaei; S Hemati (Tehran University of Medical Sciences, 2007)
Background: Urinary tract Infections is the most frequently diagnosed kidney and urologic diseases and Escherichia coli is the most common pathogen found in urinary tract infections. The most frequent serogroups determined in the P- fimbriated strains belonged to one of the six serogroups O1, O2, O4, O6, O7, O18. In E. coli strains, the P fimbriae are considered an essential virulence factor causing pyelonephritis the pap operon encodes for the p fimbriae adhesion. Methods: 130 E. coli strains were isolated from 130 patients with UTI, symptoms and bacteriuria >105 CFU/ml. All of the isolated E. coli were serotyped using 13 different O-antisera. The DNA was released from whole organisms by boiling. Pap gene was detected in all isolated strains using PCR. Pap1 and pap2 25-mer primers were used for PCR and DNA target segment were 328 bp. Results: Serogroups O6(23.84%), O18(12.30%) and O15(6.93%) were the predominant serogroups, respectively. The 44 strains (33.86%) were non-typeable and 61% strains in this study were positive for the pap operon. Conclusion: The pap operon investigated in this study was particularly present in strains belonging to 4 sero-groups most frequently detected in uropathogenic E. coli. Urinary tract infection are caused by a limited number of uropathogenic E.coli strains that predominant possess the pap adhesion-encoding operons.